2015
DOI: 10.1177/1559827615605789
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Health Promotion in the 21st Century

Abstract: The purpose of this article is to synthesize developments from various disciplines including the medical, wellness, psychology, and sociology fields to shed light on where health promotion is headed in the next 25 years. Lifestyle medicine practitioners will continue to play a large role in helping people achieve the highest levels of wellness, which does not simply mean the absence of disease. New research identifies the important roles of many diverse factors such as relationships, lifestyle behaviors, emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…Our understanding of health and the impact of behavioral, sociocultural, and system-level factors on health outcomes has evolved significantly over the past several decades [1]. Advances in technology are central to this evolution, as adoption of mobile devices connected to the Internet continues to grow across sociodemographic groups and geographic regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding of health and the impact of behavioral, sociocultural, and system-level factors on health outcomes has evolved significantly over the past several decades [1]. Advances in technology are central to this evolution, as adoption of mobile devices connected to the Internet continues to grow across sociodemographic groups and geographic regions.…”
Section: Introductionmentioning
confidence: 99%
“…Social media is defined as activities, practices, and behaviors among communities of users who gather online to share information, knowledge, and opinions using conversational media [3]. There are tens of thousands of health-promotion-related social media websites that are currently available to the public [1]. In health promotion, social media is commonly accessed for networking and community building purposes, as well as for informing healthcare decision-making between patients and providers [4].…”
Section: Introductionmentioning
confidence: 99%
“…Prototypes and applications exist in several of these fields. E.g., within health care, a wide range of applications have been identified, such as hands-free photo and video documentation, telemedicine, Electronic Health Record retrieval and input, rapid diagnostic test analysis, education, and live broadcasting (Stefan Mitrasinovic et al 2015), as well as health promotion (Edington et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(Dee W. Edington, 2015) The same authors believe that the successful wellness programs of the future are those that focus on the social and emotional context of a supportive workplace, culture, and environment. (Edington, Schultz, Pitts, & Camilleri, 2016) Historically, financial incentives and participation in wellness programs have been the primary measures of success. However, financial gains for the company or participation by an employee only demonstrate short term results.…”
Section: Theme #2: the Future Of Workplace Wellness Will Require An Umentioning
confidence: 99%
“…They describe "next practices" as those that focus on the social and emotional context of a supportive workplace, culture, and environment. (Edington et al, 2016) Recent research has found that employees are skeptical of health practices unless they are sure the practices are in the employees' best interests, not just the financial interests of the company. (Dee W. Edington, 2015) Further ways that organizations can demonstrate overall support is to provide incentives or competitions to drive behavioral change in employees.…”
Section: )mentioning
confidence: 99%